The Megamaser Cosmology Project − XII. VLBI imaging of H2O maser emission in three active galaxies and the effect of AGN winds on disc dynamics. Issue 2 (18th August 2020) - Kuo, C Y; Braatz, J A; Impellizzeri, C M V; Gao, F; Pesce, D; Reid, M J; Condon, J; Kamali, F; Henkel, C; Greene, J E
ABSTRACT: We present very long baseline interferometry (VLBI) images and kinematics of water maser emission in three active galaxies: NGC 5728, Mrk 1, and IRAS 08452–0011. IRAS 08452–0011, at a distance of ∼200 Mpc, is a triple-peaked H2 O megamaser, consistent with a Keplerian rotating disc, indicating a black hole mass of (3.3± 0.2)× 10^7 M_ . NGC 5728 and Mrk 1 display double-peaked spectra, and VLBI imaging reveals complicated gas kinematics that do not allow for a robust determination of black hole mass. We show evidence that the masers in NGC 5728 are in a wind while the Mrk 1 maser system has both disc and outflow components. We also find that disturbed morphology and kinematics are a ubiquitous feature of all double-peaked maser systems, implying that these maser sources may reside in environments where active galactic nucleus (AGN) winds are prominent at ∼1 pc scale and have significant impact on the masing gas. Such AGNs tend to have black hole masses M_BH 8 × 10 6 M⊙ and Eddington ratios λ _Edd 0.1, while the triple-peaked megamasers show an opposite trend.